Manolo Blahník and the tale of the elves and the shoemaker - Morton, Camilla; Blahník, Manolo, 1942- (New York : Itbooks, HarperCollins, 2011)
Fashion writer Camilla Morton inventively reimagines the fairy tale, blending it with the real life story of the fashion designer Manolo Blahnik. Blahnik's illustrations take us from the banana plantations of his childhood to this current reign at the top of high-fashion footwear design.
"A fashion fairy tale memoir"--Jacket.
boek
Keywords: Blahnik, Manolo, -- 1942-